Cost‐effectiveness of supervised exercise therapy compared with endovascular revascularization for intermittent claudication. Issue 12 (11th August 2016) - van den Houten, M. M. L.; Lauret, G. J.; Fakhry, F.; Fokkenrood, H. J. P.; van Asselt, A. D. I.; Hunink, M. G. M.; Teijink, J. A. W.
Abstract: Background: Current guidelines recommend supervised exercise therapy (SET) as the preferred initial treatment for patients with intermittent claudication. The availability of SET programmes is, however, limited and such programmes are often not reimbursed. Evidence for the long‐term cost‐effectiveness of SET compared with endovascular revascularization (ER) as primary treatment for intermittent claudication might aid widespread adoption in clinical practice. Methods: A Markov model was constructed to determine the incremental costs, incremental quality‐adjusted life‐years (QALYs) and incremental cost‐effectiveness ratio of SET versus ER for a hypothetical cohort of patients with newly diagnosed intermittent claudication, from the Dutch healthcare payer's perspective. In the event of primary treatment failure, possible secondary interventions were repeat ER, open revascularization or major amputation. Data sources for model parameters included original data from two RCTs, as well as evidence from the medical literature. The robustness of the results was tested with probabilistic and one‐way sensitivity analysis. Results: Considering a 5‐year time horizon, probabilistic sensitivity analysis revealed that SET was associated with cost savings compared with ER (−€6412, 95 per cent credibility interval (CrI) –€11 874 to –€1939). The mean difference in effectiveness was −0·07 (95 per cent CrI −0·27 to 0·16) QALYs. ER was associated with an additional €91 600 per QALY gained compared with SET. One‐way sensitivity analysis indicated more favourable cost‐effectiveness for ER in subsets of patients with low quality‐of‐life scores at baseline. Conclusion: SET is a more cost‐effective primary treatment for intermittent claudication than ER. These results support implementation of supervised exercise programmes in clinical practice. Abstract : Supervised exercise more cost‐effective